2022
DOI: 10.3390/w14121838
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Potential Assessment Using GIS and Remote Sensing Techniques: Case Study of West Arsi Zone, Ethiopia

Abstract: Groundwater is a crucial source of water supply due to its continuous availability, reasonable natural quality, and being easily diverted directly to the poor community more cheaply and quickly. The West Arsi Zone residents remain surface water dependent due to traditional exploration of groundwater, which is a tedious approach in terms of resources and time. This study uses remote sensing data and geographic information system techniques to evaluate the groundwater potential of the study area. This technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 54 publications
2
8
0
2
Order By: Relevance
“…While all three parameters contributed to the delineation of groundwater prospect zones, soil texture exhibited the most significant influence, as demonstrated by its high mean rank value of 8.92. This further corroborates findings reported by Kabeto et al [62] in their study. Although Ld was included in the analysis, it demonstrated a minimal impact on the mapping and assessment of groundwater prospects.…”
Section: Optimum Factors For Delineating Gwp Zonessupporting
confidence: 94%
See 1 more Smart Citation
“…While all three parameters contributed to the delineation of groundwater prospect zones, soil texture exhibited the most significant influence, as demonstrated by its high mean rank value of 8.92. This further corroborates findings reported by Kabeto et al [62] in their study. Although Ld was included in the analysis, it demonstrated a minimal impact on the mapping and assessment of groundwater prospects.…”
Section: Optimum Factors For Delineating Gwp Zonessupporting
confidence: 94%
“…Taking into consideration the inclusion of surface elevation, many other researchers have assured the rationality of surface elevation and its role as being an important factor influencing groundwater potential. For example, a study by Kabeto et al [62] found that elevation was among the most significant elements affecting groundwater potential in the West Arsi Zone of Ethiopia. Another study by Hasanuzzaman et al [58] found that elevation was one of the main features manipulating groundwater potential in the Chota Nagpur Plateau of India.…”
Section: Optimum Factors For Delineating Gwp Zonesmentioning
confidence: 99%
“…Most of the research done in Ghana on water quality assessment used a statistical and multivariate approach in assessing the quality of the groundwater source for drinking and irrigation purposes. Research done by Arnold et al [ 2 ], Boateng et al [ 6 ], Hayford & Appiah-Adjei [ 7 ], and Sander et al [ 13 ] failed to determine spatially the groundwater zones and quality similar to works by Hagos & Andualem [ 14 ], Kabeto et al [ 15 ], Rahmati et al [ 16 ], and Saranya & Saravanan [ 17 ]. The purpose of this study is to create continuous surface and maps of groundwater quality data, which will help to identify areas where groundwater quality parameters exceed the acceptable limits.…”
Section: Introductionmentioning
confidence: 92%
“…In addition, compacted sediment, which limits the pores, affects infiltration ability. Lithology is a parameter controlling groundwater potential because it influences the characteristics of aquifer materials such as porosity and permeability (Ayazi et al, 2010;Kabeto et al, 2022). The groundwater potential obtained is slightly different between solid and loose sediments in the Serayu watershed, but both are in the moderate to good category.…”
Section: Lithology Impactmentioning
confidence: 99%
“…In contrast, vegetated land cover (e.g. agricultural land and forest) contributes positively to groundwater potential due to higher infiltration (Kabeto et al, 2022;Li et al, 2018;Singh et al, 2010).…”
Section: Land Use/land Covermentioning
confidence: 99%